The pathological significance of LOXL2 in pre-metastatic niche formation of HCC and its related molecular mechanism. (April 2021) - Wu, Sifan; Xing, Xiaoxia; Wang, Yaohui; Zhang, Xi; Li, Miao; Wang, Mimi; Wang, Zhiming; Chen, Jie; Gao, Dongmei; Zhao, Yan; Chen, Rongxin; Ren, Zhenggang; et al.
Abstract: Objective: The mechanisms underlying the contribution of primary tumour to pre-metastatic niche formation remains largely unknown in hepatocellular carcinoma (HCC). We previously reported that the released LOXL2 from HCC cells under higher stiffness stimulation facilitated the formation of lung pre-metastatic niche. Here, we further clarified the pathological role of LOXL2 in promoting lung pre-metastatic niche formation and lung metastasis occurrence in HCC and its relevant molecular mechanism. Methods: Using two different animal models and an in vitro system of mechanically tuneable gel mirroring lung tissue stiffness, we explored the underlying mechanism of LOXL2 in pre-metastatic niche formation. Results: We applied tail vein injection of CM-LV-LOXL2-OEsimulating tumour-released soluble factors to induce lung pre-metastatic niche formation and found that the injected LOXL2 remarkably enhanced CD11b + /CD45 + bone marrow-derived cells (BMDCs) recruitment and fibronectin expression in lung. Subsequently, LOXL2-overexpressed xenograft HCC models validated that tumour-secreted LOXL2 significantly promoted the occurrence of pulmonary metastasis. In vitro, LOXL2 and LOXL2-caused matrix stiffening not only obviously upregulated the expressions of MMP9 and fibronectin in lung fibroblasts, but also evidently increased the number of adherent HCC cells and the expression of chemokine CXCL12. The activation of PI3K-AKT pathway mediated LOXL2-upregulated fibronectin. HCC patients in High-LOXL2 group had higher ratio of tumour recurrence than HCC patients in Low-LOXL2 group, supporting a significance of LOXL2 in HCC progression and unfavourable outcome. Conclusion: Primary tumour-released LOXL2 promotes lung pre-metastatic niche formation and lung metastasis occurrence. LOXL2-caused matrix stiffening synergistically regulates lung pre-metastatic niche formation. Targeting LOXL2-induced lung pre-metastatic niche may be a novel intervention approach against HCC metastasis. Highlights: LOXL2 promotes lung pre-metastatic niche formation and lung metastasis occurrence. LOXL2-caused matrix stiffening also contributes to pre-metastatic niche formation. Targeting LOXL2-induced pre-metastatic niche may be an intervention approach.